2003
DOI: 10.1001/archinte.163.10.1172
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Periodontal Disease and C-Reactive Protein Among Adults in the Atherosclerosis Risk in Communities Study

Abstract: Extensive periodontal disease and BMI are jointly associated with increased CRP levels in otherwise healthy, middle-aged adults, suggesting the need for medical and dental diagnoses when evaluating sources of acute-phase response in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(140 citation statements)
references
References 31 publications
10
126
1
1
Order By: Relevance
“…In addition, the results from this study and other reports findings that also showed a relationship between C-reactive protein and periodontal disease 14,24,25 suggesting that this relationship could be of public health relevance. For example, if one of the objectives of a weight reduction program is to reduce a proinflammatory state then evaluation of the patient's periodontal status is important to effectively reduce hs-CRP levels.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, the results from this study and other reports findings that also showed a relationship between C-reactive protein and periodontal disease 14,24,25 suggesting that this relationship could be of public health relevance. For example, if one of the objectives of a weight reduction program is to reduce a proinflammatory state then evaluation of the patient's periodontal status is important to effectively reduce hs-CRP levels.…”
Section: Discussionsupporting
confidence: 75%
“…Results of several randomized clinical trials corroborate the current view that periodontal treatment is effective in reducing hs-CRP levels; 26 this underlines the importance of good oral health in maintaining systemic health. 25 Accordingly, health promotion programs that are designed to assist obese patients to lose weight and reduce the risks of cardiovascular disease should include oral health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…CRP was quantified using ELISA assay (range of detection 0.5–50 mg/l) 52. Intra-plate and inter-plate coefficients of variation ranged from 0–37.3% and 0–10.6%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…6 Periodontal infections are also associated with increases in systemic markers of inflammation including biomarkers such as C reactive protein. 13 By analogy, edentulism is commonly associated with denture infections (denture mucositis) which induce mucosal inflammation and unclean dentures can also pose as a chronic reservoir of oral pathogens. However, the potential role of denture-based infection as a potential risk factor for COPD remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%